Molecular Characterization of the Multidrug Resistant Escherichia coli ST131 Clone - Mark A. Schembri; Nouri L. Ben Zakour; Minh-Duy Phan; Brian M. Forde; Mitchell Stanton-Cook; Scott A. Beatson (Pathogens, 2015)
Escherichia coli ST131 is a recently emerged and globally disseminated multidrug resistant clone associated with urinary tract and bloodstream infections in both community and clinical settings. The most common group of ST131 strains are defined by resistance to fluoroquinolones and possession of the type 1 fimbriae fimH30 allele. Here we provide an update on our recent work describing the globally epidemiology of ST131. We review the phylogeny of ST131 based on whole genome sequence data and highlight the important role of recombination in the evolution of this clonal lineage. We also summarize our findings on the virulence of the ST131 reference strain EC958, and highlight the use of transposon directed insertion-site sequencing to define genes associated with serum resistance and essential features of its large antibiotic resistance plasmid pEC958.